AN ANALYSIS ON COMMUNITY IDENTITY FOR DEVELOPING TOURIST DESTINATION THROUGH PARTICIPATION PROCESS, TAI YUAN AND LAO KRANG COMMUNITY, KAMPHAENG SAEN DISTRICT, NAKHON PATHOM PROVINCE - Srirak, Chainarong; Suttipisan, Sutsan (Journal of Liberal Arts and Management Science Kasetsart University, 2020)
The purposes were to: study context Tai Yuan and Lao Krang cultural community, and conduct analysis on community identity through participation process of Tai Yuan and Lao Krang cultural community, and to develop tourism model and activity of community under identity of Tai Yuan and Lao Krang culture, Kamphaeng Saen District, Nakhon Pathom Province. This study was a participatory research. The qualitative data was gathered through semi-structured in-depth interview, focus group and participant observation. The quantitative data was acquired through agricultural tourism potential evaluation form. The self-analysis process was conducted with 60 cases including community leaders and villagers. The findings reveal that Huai Muang Community has high potential in agricultural tourism. The major activity was shrimp farming. The Tai Yuan and Lao Krang ethnic people settled the community about 300 years ago. They presently have 4 points of outstanding community identity including dwelling, language, food and dressing. These are indicators of tourism potential at high level and suitable for tourist destination development. The tourism model and activities under community identity are shrimp farming, Tai Yuan textile weaving, Palang (dining), “Somma Khan Mak Beng” performing art at cultural square. The analysis on community identity for developing community tourist destination results in driving strong community tourist destination through learning of knowledge, skill and attitude of stakeholders as well as promoting relationship system among community members. This allows community members to participate in community development.